Kemunduran Kualitas Pupuk Hayati Rhizobium - Prihastuti Prihastuti; A. Harsono (Sains dan Matematika, 2012)
This is a descriptive analytical research to describe the quality deterioration of Rhizobium bio-fertilizer product during storage. The material was used a Rhizobium bio-fertilizer in plastic packing, which was stored in an incubator by temperature of 28oC for nearly ten months. The results showed that there had been a defect in the sealing plastic and formed small holes, caused the contamination, evidently by the growth of bacterial colonies were diverse. The analysis of C, N, P and K content indicated that career matter of bio- fertilizer composition belong to the dignity of the high fertility to support microbial growing. Total population of microbes in Rhizobium bio-fertilizer of all observed samples >106 cfu/g, but could not be considered a total population of Rhizobium. The damage of sealing packing decreased of the moisture career matter and become a limiting factor to support microbial viability. It was recommended to use a better quality plastic with appropriate sealing system.